Health impact of work stressors and psychosocial perceptions among French hospital workers during the COVID-19 outbreak: a cross-sectional survey - Jean-Dominique Dewitte; Brice Loddé; Richard Pougnet; David Lucas; Sandrine Brient; Bisi Moriamo Eveillard; Annabelle Gressier; Tanguy LeGrand (BMJ Open)
Objective To compare global health, mental health impact of work stressors and psychosocial perception of healthcare workers (HCWs) and non-HCWs in a hospital after the first peak of the COVID-19 outbreak in France.Methods A validated version of the SATIN (Santé Au Travail Inrs université Nancy 2)questionnaire with adapted scoring was used to collect data on health and impact of work stressors. This questionnaire was sent to all workers at a hospital in July 2020 and was self-administered online. In a multinomial regression model, we included HCW status, age, gender and front-line worker status as covariates.Results Data from a total of 1405 participants were included. We found that being an HCW, male and front-line worker was a risk factor for negative perception of work demand (OR 7.35, 95% CI 4.2 to 11.47; OR 2.55, 95% CI 1.11 to 5.89; OR 1.78, 95% CI 1.04 to 3.06). Being an HCW was a predictive factor for stress (OR 1.47, 95% CI 1.04 to 2.08), poor global health (OR 1.71, 95% CI 1.14 to 2.55) and negative perception of work activity environment (OR 1.9, 95% CI 1.3 to 2.8).Conclusion We have shown that all HCWs suffered from some health impact shortly after the first peak of the COVID-19 outbreak. We underline some stressors with high impact, including work demand, work abilities and organisational context, and emphasise the need for risk management.